2019
DOI: 10.1002/phar.2212
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prophylactic Heparin Dosage Strategies and Risk Factors for Venous Thromboembolism in the Critically Ill Patient

Abstract: Background Venous thromboembolism (VTE) occurs frequently in critically ill patients without heparin prophylaxis. Although heparin prevents VTE, VTEs occur frequently despite prophylaxis. A higher heparin dosage may be more effective for preventing VTE. Methods A retrospective study was conducted using the Premier Incorporated Perspective Database to evaluate comparatively the effects of different heparin prophylaxis dosing strategies in the critically ill patient. Critically ill adult patients who were mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
3
14
0
2
Order By: Relevance
“…Our data on hypercoagulable features in non-liver septics are consistent with clinical observations of an increased risk of both venous and arterial thrombosis in these patients, even in patients receiving optimal pharmacological thromboprophylaxis. [33][34][35][36] In addition, the hypercoagulable features might contribute to microvascular thrombotic events that have been linked to organ failure. 37 The usefulness of anticoagulant therapy to treat the hypercoagulable features of sepsis and sepsis-associated disseminated intravascular coagulation have been debated given the mixed results of clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our data on hypercoagulable features in non-liver septics are consistent with clinical observations of an increased risk of both venous and arterial thrombosis in these patients, even in patients receiving optimal pharmacological thromboprophylaxis. [33][34][35][36] In addition, the hypercoagulable features might contribute to microvascular thrombotic events that have been linked to organ failure. 37 The usefulness of anticoagulant therapy to treat the hypercoagulable features of sepsis and sepsis-associated disseminated intravascular coagulation have been debated given the mixed results of clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…To spare the necessary patient contact involved, a preference developed for apixaban, which has been used as prophylaxis for patients with cancer, in acute infectious diseases, and in orthopedic thromboprophylaxis with success. [21][22][23] Decision support in our electronic medical record for prophylactic subcutaneous heparin dosing follows Micromedex recommendation, which refers to a study by Reynolds et al 24 that found no difference in every 12 hour and every 8 hour dosing. Our institution practice, however, is to use every 8 hours dosing for patients with a BMI of greater than 30.…”
Section: Discussionmentioning
confidence: 99%
“…Las alteraciones hematológicas representaron la mayor frecuencia de eventos adversos de forma conjunta, y se identificaron casos con presencia de sangrado (equimosis, gingivorragia, epistaxis, hematuria, hematoma, HVDA, HVDB y petequias) en porcentajes diversos. En este sentido, se refiere en la literatura que con HBPM se presenta una tasa de sangrado mínima [55][56][57], así como también para warfarina [58], rivaroxabán [59] y dabigatrán [60]; en el estudio no se presentaron eventos adversos con estos 2 últimos NOAC, pero en los casos positivos la diversidad de tratamientos puede estar relacionada.…”
Section: Discussionunclassified